Bursal-Derived BP7 Induces the miRNA Molecular Basis of Chicken Macrophages and Promotes the Differentiation of B Cells - Jiaxi Cai; Ze Zhang; Chenfei Li; Shanshan Hao; Anran Lu; Xiangyu Huang; Xiuli Feng (Vaccines, 2022)
The bursa of Fabricius (BF) is a vital central humoral immune organ unique to birds. The bioactive peptide BP7 derived from bursa is reported to promote the vaccine immune response and antibody production. However, the regulatory effect on antigen presentation and B cell differentiation has been infrequently reported. In this paper, chicken macrophage HD11 cells were used for the cell model, and the cellular molecular expressions were determined by the fluorescent quantitative PCR (qPCR) after BP7 treatment. Then, the miRNA expression profile was analyzed by high-throughput sequencing. In addition, BALB/C mice were used as the animal model to detect B cell subtype with flow cytometry (FCM). The results showed that the expressions of four immune active molecules, IL-1β, IL-6, iNOS, and IFN-α, in HD11 cells were significantly increased with 100 ng/mL BP7 treatment. Compared with the control group, there were 58 up-regulated and 61 down-regulated miRNAs in HD11 cells with BP7 treatment. The gene ontology (GO) function analysis found that BP7 mainly affected the various biological processes, molecular function, and MHC protein complex. Pathway analysis showed that 100 ng/mL BP7 stimulated various physiological metabolic pathways and signal transduction pathways, including the intestinal immune network producing IgA in HD11 cells. Furthermore, it was found that BP7 in vitro stimulated B cell populations, as well as plasma cells in spleen cells from the immunized mice. Additionally, B cell activation subpopulations were increased in mice immunized with the AIV vaccine and BP7. These results proved that BP7 stimulated various differentially expressed genes in chicken macrophage HD11 cells, and induced B cell differentiation in the immunized mice, which suggested that BP7 might participate in the antigen presentation process, thereby promoting the differentiation of B cells. These results provide an important basis for the mechanism of bursal-derived peptide on B cell development, and offer the experimental basis for the development of adjuvants.